Development of “OrigamiGo” for enhancing visualization skills based on origami art - Mohd Salehudin Marji; Aede Hatib Musta’amal; Nor Aisyah Che Derasid; Mohd Halimi Ab Hamid; Ghany Taufik Sidik (Journal of Education and Learning (EduLearn), 2026)
Visualization skills are essential in engineering education, yet many Malaysian students struggle to develop them, which affects their performance in Grafik Komunikasi Teknikal, also known as technical drawing. This study evaluated the effectiveness of OrigamiGo, a paper-folding-based teaching module, in improving students’ visualization skills. Unlike computer-based tools, OrigamiGo provides low-cost, tactile, hands-on learning experiences that integrate visual and haptic activities. A quasi-experimental design was conducted with 36 tenth-grade students from two secondary schools in Johor, Malaysia. Students’ visualization skills were measured using a validated test instrument, and data were analyzed using inferential statistics in SPSS. The experimental group showed significantly greater improvement than the control group, with mean N-gain scores of 57.85 and 20.41, respectively. Paired t-tests showed significant pre-to-post test improvements in both groups. The independent t-test revealed a significant difference in post-test scores, with the experimental group scoring higher than the control group (21.32 vs. 17.29). These findings indicate that OrigamiGo is an effective alternative approach for enhancing visualization skills in technical and vocational education. Future studies may examine its application in broader educational contexts and larger samples.